Rising Islamic Conservatism in Indonesia Islamic Groups and Identity Politics - Azimah, Yutsrina (Universitas Islam Internasional Indonesia, 2022)
Edited by Leonard C. Sebastian, Syafiq Hasyim and Alexander R. ArifiantoIndonesia entered the new order Era in the mid-1998 or post-Suharto era, which served as a significant transitional period that gave rise to a range of ideas, identities, and interests to the surface (Hefner 2005; Hasan 2006, 13; Hilmy 2010). One of them is the emergence of Islamic conservatism movements (Hilmy 2010). Consequently, the new and various transnational Islamic movements that emerged in that era have colored the landscape of Indonesian Islam. The term conservative itself refers to currents that reject progressive interpretations of Islamic teachings (van Bruinessen 2013). The separation of modernist and conservative groups cannot be separated from the current political tendencies in Indonesia, particularly in the quest for power. Political polarization using religion to mobilize the masses has been an inseparable thing in Indonesia (Warburton, n.d.). The post-Suharto era became one of the decisive elements since it did not accommodate the conservative spectrum of Islam (Mietzner and Muhtadi 2018).